35 aniversario UNED. (UNED, 2012)
Vista del auditorio, grupo grande de personas, aparecen entre otros: Leonardo Garnier, Luis Guillermo Carpio, Humberto Aguilar, Ilse Gutiérrez, Joaquín Jiménez, Orlando Morales, Katya Calderón, Edgar Castro, Rodrigo Arias, Celedonio Ramírez, Francisco Antonio Pacheco, Chester Zelaya, Roberto Román, Luis Fernando Fallas